Implementasi Patient Safety Berbasis Kearifan Lokal - Ida Ayu Putu Widyastuti (Universitas Pendidikan Nasional, 2018)
ABSTRACTPatient safety is a variable to measure and evaluate the quality of health services. Implementation of patient safety program can not run optimally if the competence and values or culture not support. Purposes of this research to identify and interpret the existence of local wisdom values applied in the implementation of patient safety in Puri Raharja General Hospital. Research design used a qualitative approach. The research informants amounted to 8 people consist of the management of nursing, nurses in the ward as well as the patients determined through the inclusion and exclusion criteria. The results showed that the value of local wisdom that is implemented in patient safety is the embodiment of Tri Hita Karana implementation which is the three source that bring safety with the implications of Catur Marga on the concept of Parahyangan and Tat Twam Asi on the concepts of Pawongan. Catur Marga Concepts is widely implemented in an effort to achieve the patient safety goals and reporting of patient safety incidents, and the basic principles of “Tat Twam Asi” conceived into “paras paros and salulung sabayantaka”. This philosophy is a sense of shared destiny, kinship and mutual cooperation in achieving the same goal for patient safety is widely implemented in effective communication between nurses and other health teams. Suggest for RSU Puri Raharja to instill all employees of the patient safety culture as the primary goal and shared responsibility by not abandoning local values, sothat all health care workers participate in the patient safety culture.